THE PHONOLOGICAL PROCESS OF THE SUFFIX /-i/ IN THE JAVANESE LANGUAGE: A GENERATIVE PHONOLOGY APPROACH - Al Haris, Ulin Nuha (LANTERN (Journal on English Language, Culture and Literature), 2017)
This research explains the Javanese sound distribution, the sound change that is caused by the suffix /-i/, and the phonological process of the base word that is attached by the suffix /-i/. The data used in this study are from the utterances of Javanese native college students from Semarang, Kendal, and Solo. The result shows that the distribution is divided into two based on the position. Besides, in Javanese, the suffix /-i/ has the functions, which are (1) to change the part of speech, (2) to show the passive verb, (3) to show the repetitive action. The result also shows that there are two phonological processes that are caused by the suffix /-i/. They are addition of the /n/ consonant and the vowel weakening.